Kelimpahan Cacing Tanah pada Beberapa Jenis Tegakan Pohon di Wanagama I - Haryono Supriyo; Musyafa Musyafa; Arom Figyantika; Saptuti Gamayanti (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Earthworms feed exclusively on dead organic matter (OM). The earthworm population is regulated by organic matter availability and soil characteristics. The aim of the research was to investigate the effect of seasonal change to the abundance and biomass of earthworms in Wanagama I. Collection of the soil samples was conducted from a quadrangle 25 x 25x 25 cm with the depth of 0-10, 10-20 and 20-30 cm with 5 replications under stands of Glyricidae, Leucaena, Teak, Acacia, Eucalyptus and Mahogany. Soil samples were taken at rainy season (February), early dry season (July) and dry season (October) 2004. The earthworms were manually extracted from soil samples and the abundance was stated as number and biomass of dry weight. The result showed the abundance and biomass of earthworms were high only in February at the soil depth of 0-10 cm. The highest number of earthworm and biomass was found in Mahogany stand (224,000 individual.ha-1/105.6 kg.ha-1). Multiple linier regression analysis showed that abundance of earthworms was affected by soil moisture content, while the biomass of earthworms was affected by soil pH and bulk density (aeration).